PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI DI SEKRETARIAT DAERAH KOTA TANGERANG - Effendi AK; Irfan Azhar (Gapenas Publisher, 2021)
Tangerang City Regional Secretariat as part of the government bureaucratic organization must have basic assumptions, values ??and artifacts that means workmanship inherent in it as a work culture that has existed for a long time. Therefore, as part of the management of public organizations, a review of the organization is still very up to date for examination. This penelitiaan put three pieces of variables that style of leadership, workplace culture and employee performance. To analyze the relationship between these variables used quantitative methods to the type of associative. As a base material used analysis of respondents' perception that the employees who work at the Regional Secretariat Tangerang totaling 84 people from the existing 168 employees. With the data analysis technique used is using product moment correlation coefficient, determination coefficient, and linear regression. Results of research positive influence between leadership style and work culture to employee performance that form the linear regression equation of Y = 15.741 + 0,246X1 + 0,307X2. In detai effect of each variable is : The contribution of leadership style on employee performance of 14.59%, which the regression model can be used to predict one's leadership style can improve employee performance by 0.332. Ability to work without the help of cultural variables other variables contributing to the improved performance of employees amounted to 19.18%, which the regression model can be used to predict the performance improvement of employees amounted to 0.373. In conditions remain variable leadership style and work culture without the help of other variables simultaneously contributes to the increased performance of employees amounted to 31.47%, which the regression model can be used to predict one's leadership style can improve employee performance amounted to 0.246, and the time work culture can improve the performance of employees amounted to 0.307. In order for the performance of employees in these offices can be further optimized, then it should be carried out further research on variable epsilon, because the weight is quite large, amounting to 68.53%, compared to the study variables